Desain dan Analisa Perhitungan Rem Cakram Pada Mobil Sport Utility Vehicle (SUV) - Eko Ari Wibowo; Widyastuti; Muhammad Nur Wahyu Hidayah; Ida Betanursanti (Politeknik Negeri Cilacap, 2023)
Brakes are an important component in a vehicle unit, so it is necessary to have proper planning in the design and manufacture process. The purpose of this study is to design disc brakes on a Sport Utility Vehicle (SUV) car with consideration of the results of the calculation analysis based on the specifications of the reference car. The resulting design is in the form of main components which include calipers, pistons, discs, pads, rivets, pins and bolts. Based on this design, the calculation results show the braking process when a car traveling at a speed of 245 km/h can stop at a braking distance (s) of 42 m with a braking time 4 seconds. The next research is to make a mathematical model to optimize the dimensions of the brake components needed at the ideal braking distance.